A Call for Standardization in Platelet-Rich Plasma Preparation Protocols and Composition Reporting: A Systematic Review of the Clinical Orthopaedic Literature. (18th October 2017) - Chahla, Jorge; Cinque, Mark E.; Piuzzi, Nicolas S.; Mannava, Sandeep; Geeslin, Andrew G.; Murray, Iain R.; Dornan, Grant J.; Muschler, George F.; LaPrade, Robert F.
Abstract : Background: Platelet-rich plasma (PRP) is a blood-derived preparation whose use has grown exponentially in orthopaedic practice. However, there remains an unclear understanding of the biological properties and effects of PRP on musculoskeletal healing. Heterogeneous processing methods, unstandardized nomenclature, and ambiguous classifications make comparison among studies challenging. A comprehensive assessment of orthopaedic clinical PRP trials is key to unraveling the biological complexity of PRP, while improving standardized communication. Toward this goal, we performed a systematic review of the PRP preparation protocols and PRP composition utilized in clinical trials for the treatment of musculoskeletal diseases. Methods: A systematic review of the literature was performed from 2006 to 2016. Inclusion criteria were human clinical trials, English-language literature, and manuscripts that reported on the use of PRP in musculoskeletal/orthopaedic conditions. Basic-science articles, editorials, surveys, special topics, letters to the editor, personal correspondence, and nonorthopaedic applications (including cosmetic use or dental application studies) were excluded. Results: A total of 105 studies (in 104 articles) met the inclusion criteria for analysis. Of these studies, only 11 (10%) provided comprehensive reporting that included a clear description of the preparation protocol that could be used by subsequent investigators to repeat the method. Only 17 studies (16%) provided quantitative metrics on the composition of the final PRP product. Conclusions: Reporting of PRP preparation protocols in clinical studies is highly inconsistent, and the majority of studies did not provide sufficient information to allow the protocol to be reproduced. Furthermore, the current reporting of PRP preparation and composition does not enable comparison of the PRP products being delivered to patients. A detailed, precise, and stepwise description of the PRP preparation protocol is required to allow comparison among studies and provide reproducibility.